2021
DOI: 10.3389/fphys.2021.697022
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Placental Mitochondrial Respiration in Tibetan Women at High Altitude

Abstract: Living at high altitudes is extremely challenging as it entails exposure to hypoxia, low temperatures, and high levels of UV radiation. However, the Tibetan population has adapted to such conditions on both a physiological and genetic level over 30,000–40,000 years. It has long been speculated that fetal growth restriction is caused by abnormal placental development. We previously demonstrated that placentas from high-altitude Tibetans were protected from oxidative stress induced by labor compared to those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Further, Liu et al. 121 discovered that human placental mitochondrial respiration was greater in high-altitude than in lower-altitude Tibetan women. The authors suggested that the increased mitochondrial respiration in placentas from Tibetan women with a prolonged high-altitude residence ancestry may represent an adaptive response to remedy the increased energy demand and oxidative stress imposed by labor in an oxygen-deprived environment.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Liu et al. 121 discovered that human placental mitochondrial respiration was greater in high-altitude than in lower-altitude Tibetan women. The authors suggested that the increased mitochondrial respiration in placentas from Tibetan women with a prolonged high-altitude residence ancestry may represent an adaptive response to remedy the increased energy demand and oxidative stress imposed by labor in an oxygen-deprived environment.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the increase in mitochondrial respiration, namely the OXPHOS capacity via complexes I and I + II, ET capacity, and non-phosphorylating respiration has been recently reported to occur as an adaptive change in placentas harvested after laboring vaginal delivery from Tibetan women living to high-altitude (3780 m) as compared to lower-altitude (2261 m) [ 42 ]. Accordingly, it is tempting to speculate that in the setting of preeclampsia, the increase in placental mitochondrial respiration is an adaptive mechanism that occurs in pregnancies without (but not anymore in those with) FGR.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there were no differences observed in the gene expression profiles of placentas from high-altitude Tibetan women delivered vaginally versus those delivered via cesarean section, indicating a blunted response to acute ischemia and hypoxia among the high-altitude Tibetan population [ 7 , 8 ]. it was found that pregnant Tibetan women living at high altitudes exhibit enhanced mitochondrial respiratory function and improved efficiency of placental oxidative phosphorylation [ 4 ]. In this experimental study, we discovered that the protein expression patterns in the placentas of the low-altitude Tibetan group were similar to those of the low-altitude Han Chinese group.…”
Section: Data Descriptionmentioning
confidence: 99%
“…However, little is known about the changes in placental protein expression during natural delivery. Previous studies have found that the respiratory function of mitochondria in high-altitude Tibetan placentas is enhanced, the mitochondria in the placenta are less, the content of complexes is high, and the efficiency of placental mitochondria in utilizing oxygen is improved [ 4 ]. In this study, we aimed to reveal these adaptation mechanisms by studying the changes in placental protein expression during natural delivery in high-altitude Tibetans, low-altitude Tibetans, and low-altitude Han Chinese.…”
Section: Introductionmentioning
confidence: 99%